Silver nanoparticles obtained by aqueous or ethanolic aloe Vera extracts: An assessment of the antibacterial activity and mercury removal capability (2018)
Silver nanoparticles (AgNPs) were synthesized by chemical reduction of Ag+ ions (from silver nitrate AgNO3), using aqueous or ethanolic Aloe vera extracts as reducing, stabilizing, and size control agent. The nanop articles' sizes were between 2 and 7nm for ethanolic extract and between 3 and 14nm for aqueous extract, as measured by High-Resolution Transmission Electron Microscope (HRTEM). The antibacterial activity against a mesophilic microorganism, Kocuria varians, a Gram-positive coccus, was measured by counting bacterial colonies in agar plate for both extracts. We found that 4% effective concentration is the lowest concentration that completely inhibited visible growth. Mercury removal was investigated by Atomic Absorption Spectroscopy (AAS) measurements, where it was shown that it is not necessary to use high concentrations of nano particles for effective removal of mercury inasmuch as with a 20% V/V concentration of both extracts; the Hg(II) removal percentage was above 95%. These results show that the mercury remaining un removed from the different essays is below the level allowed by World Health Organization (WHO) and the Environmental Protection Agency (EPA). © 2018 Ederley Vélez et al.